Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the axis of symmetry for the quadratic equation [tex]\( y = -x^2 + 3x + 10 \)[/tex], follow these steps:
1. Identify the coefficients:
The general form of a quadratic equation is [tex]\( y = ax^2 + bx + c \)[/tex]. For the given equation [tex]\( y = -x^2 + 3x + 10 \)[/tex], we can identify the coefficients as follows:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( c = 10 \)[/tex]
2. Use the formula for the axis of symmetry:
The formula to find the axis of symmetry for a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] is [tex]\( x = -\frac{b}{2a} \)[/tex].
3. Substitute the coefficients into the formula:
Substitute [tex]\( a = -1 \)[/tex] and [tex]\( b = 3 \)[/tex] into the formula:
[tex]\[ x = -\frac{3}{2(-1)} \][/tex]
4. Simplify the expression:
Simplify the fraction:
[tex]\[ x = -\frac{3}{-2} \][/tex]
5. Calculate the result:
Simplifying further gives:
[tex]\[ x = \frac{3}{2} \][/tex]
So, the axis of symmetry for the quadratic equation [tex]\( y = -x^2 + 3x + 10 \)[/tex] is [tex]\( x = 1.5 \)[/tex]. This vertical line [tex]\( x = 1.5 \)[/tex] represents the axis of symmetry for the parabola described by the given quadratic equation.
1. Identify the coefficients:
The general form of a quadratic equation is [tex]\( y = ax^2 + bx + c \)[/tex]. For the given equation [tex]\( y = -x^2 + 3x + 10 \)[/tex], we can identify the coefficients as follows:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( c = 10 \)[/tex]
2. Use the formula for the axis of symmetry:
The formula to find the axis of symmetry for a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] is [tex]\( x = -\frac{b}{2a} \)[/tex].
3. Substitute the coefficients into the formula:
Substitute [tex]\( a = -1 \)[/tex] and [tex]\( b = 3 \)[/tex] into the formula:
[tex]\[ x = -\frac{3}{2(-1)} \][/tex]
4. Simplify the expression:
Simplify the fraction:
[tex]\[ x = -\frac{3}{-2} \][/tex]
5. Calculate the result:
Simplifying further gives:
[tex]\[ x = \frac{3}{2} \][/tex]
So, the axis of symmetry for the quadratic equation [tex]\( y = -x^2 + 3x + 10 \)[/tex] is [tex]\( x = 1.5 \)[/tex]. This vertical line [tex]\( x = 1.5 \)[/tex] represents the axis of symmetry for the parabola described by the given quadratic equation.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.